2006
DOI: 10.1074/jbc.m602057200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Evidence for the Role of the TLR2 DD Loop in TLR1/TLR2 Heterodimerization and Signaling

Abstract: The Toll/Interleukin-1 receptor (TIR) domain of the Toll-like receptors (TLRs) plays an important role in innate host defense signaling. The TIR-TIR platform formed by the dimerization of two TLRs promotes homotypic protein-protein interactions with additional cytoplasmic adapter molecules to form an active signaling complex resulting in the expression of pro-and antiinflammatory cytokine genes. To generate a better understanding of the functional domains of TLR2 we performed a random mutagenesis analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
106
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 32 publications
2
106
0
Order By: Relevance
“…The highly flexible BB loop is central to many molecular interactions involving TIR domains and adopts different conformations as observed in functional and structural studies of TLR1, TLR2, TLR10, and, recently, TLR6 (26,31,(35)(36)(37). Homodimeric molecular interactions observed in structural studies of hTLR1, hTLR2, and hTLR10 are largely mediated by residues found on the BB loop, DD loop, and α-C helix (26,31,36,37) (Fig.…”
Section: C29 Blocks Tlr2 Bacterial Agonist-induced Proinflammatory Genementioning
confidence: 99%
See 1 more Smart Citation
“…The highly flexible BB loop is central to many molecular interactions involving TIR domains and adopts different conformations as observed in functional and structural studies of TLR1, TLR2, TLR10, and, recently, TLR6 (26,31,(35)(36)(37). Homodimeric molecular interactions observed in structural studies of hTLR1, hTLR2, and hTLR10 are largely mediated by residues found on the BB loop, DD loop, and α-C helix (26,31,36,37) (Fig.…”
Section: C29 Blocks Tlr2 Bacterial Agonist-induced Proinflammatory Genementioning
confidence: 99%
“…Alanine scanning mutagenesis of all 10 BB loop pocket residues, as well as three additional mutations (Y641A, P681H, and Q747A) was performed, and their effect on TLR2/1 and TLR2/6 signaling in the absence or presence of C29 was examined using our NF-κB reporter assay. Y641A and P681H were shown previously to play a role in TLR2-MyD88 interaction (20,26), and Gautam et al (31) reported that Q747 was not important for TLR2 signaling, and therefore served as a control mutation. All 10 BB loop pocket mutants, including Y647A and P681H, were critical for TLR2/1 signaling (Fig.…”
Section: C29 Blocks Tlr2 Bacterial Agonist-induced Proinflammatory Genementioning
confidence: 99%
“…It has been shown that during these interactions, the TIR domains react with each other physically [61]. Furthermore, TIR domains condition the heterodimerization of some animal TLR receptors [62]. An analogous role of the TIR domain has been proposed for plants.…”
Section: Other Domainsmentioning
confidence: 99%
“…Despite extensive structural studies, it is not known why homotypic interactions are essential for downstream signaling (20)(21)(22)(23)(24)(25)(26)(27). To address this issue, it is necessary to discriminate residues required for homotypic and those required for heterotypic interactions.…”
mentioning
confidence: 99%